International society, global polity : an introduction to international political theory - Brown, Chris, 1945- (Los Angeles, CA : SAGE Publications, Inc., 2015)
This book provides an overview of the current state of the art in International Political Theory (IPT). It offers a coherent account of the field of IPT, placing both traditional and modern work in a clear and logical framework.
Includes bibliographical references and index.
Description based on XML content.
Keywords: International relations; Sovereignty; International law